Impact of Adjuvant Treatment in pN3 Penile Cancer. Issue 3 (March 2022) - Khurud, P.; Krishnatry, R.; Telkhade, T.; Patil, A.; Prakash, G.; Joshi, A.; Pal, M.; Noronha, V.; Menon, S.; Bakshi, G.; Prabhash, K.; Murthy, V.
Abstract: Aims: Due to the lack of high-quality evidence and consensus on adjuvant treatment for locoregionally advanced penile cancer, we reviewed the outcomes of pN3 patients to determine the suitable adjuvant treatment options. Patients and methods: All consecutive pN3 penile cancer patients treated at our institution between January 2010 and December 2018 were reviewed to assess the impact of demographical, pathological and treatment factors on disease-free survival (DFS) and overall survival. The DFS and overall survival were estimated using the Kaplan–Meier method and association was tested using the Cox regression model (two-sided test with P < 0.05 considered significant). Results: Of 128 patients, 31 (24%) had pelvic nodal involvement. Twenty-six patients (20.3%) received no adjuvant treatment, 40 (31.3%) received single modality adjuvant treatment and 62 (48.4%) received multimodality adjuvant treatment (a combination of chemotherapy and radiotherapy). At a median follow-up of 22 months, the DFS and overall survival were 55.4 and 62%, respectively. The best DFS and overall survival was noted with chemotherapy followed by concurrent chemoradiation (C-CTRT; 93% each). On multivariate analysis, both DFS and overall survival were worse with pelvic node involvement (2.2 [1.3–4], P = 0.027 and 2.2 [1.3–4], P = 0.027, respectively) and better with any adjuvant treatment (single modality: 3 [1.5–5.5], P < 0.001; multimodality: 3.1 [1.6–6], P < 0.001). C-CTRT was associated with improved DFS over chemotherapy alone (0.17 [0.4–0.78], P = 0.02) but not over radiotherapy alone (0.35 [0.07–1.6], P = 0.19). In patients with no pelvic nodes involved, chemotherapy and radiotherapy as single modalities were associated with similar DFS and overall survival. In patients with pelvic nodes, multimodality treatment was associated with better DFS than single modality treatment (0.3 [0.1–1], P = 0.05). Conclusion: pN3 penile cancer is a diverse prognostic group with poorer outcomes associated with pelvic nodes. Single modality adjuvant treatment may be adequate in inguinal nodes with extranodal extension, but multimodality treatment should be given in patients with pelvic nodal involvement. Highlights: Pelvic nodal involvement has poorer outcomes among pN3 penile cancer. Combined modality adjuvant treatment improves disease-free survival when there is pelvic nodal involvement. Single modality adjuvant treatment (CT or RT) is adequate if there is involvement of inguinal lymph node alone.